COMPONENTS OF THE METABOLIC SYNDROME IN CHILDREN AND ADOLESCENTS WITH DIFFERENT LEVELS OF VITAMIN D: A CROSS-SECTIONAL STUDY - Svetlana I. Malyavskaya; Аndrej V. Lebedev; Galina N. Kostrova (Вопросы современной педиатрии, 2017)
Background. Vitamin D is a significant risk factor for atherogenic disorders. It is of interest to study the relationship between vitamin D deficiency and the components of the metabolic syndrome, insulin resistance and markers of chronic inflammation in different age groups.Objective.  Our aim was to study association of the components  of the metabolic syndrome and pro-atherogenic  metabolic disorders with vitamin D levels in children and adolescents.Methods. In a cross-sectional (one-stage) study, the serum 25(OH)D level in children and adolescents was determined. The relationship between the 25(ОН)D level and the presence of the metabolic syndrome was assessed in quartile groups.Results. The study included 319 children and adolescents (49% — girls) aged 10–15 years. In the quartile I in terms of the 25(ОН)D level, higher (as compared with the quartile IV) mean level values of insulin (11.5 ± 6.3 and 7.3 ± 4.0 mmol/L, p <0.001), HOMA index (2.4 ± 0.8 and 1.6 ± 0.7, p <0.001), body mass index (22.6 ± 4.3 and 19.3 ± 3.9 kg/m2, p = 0.012), waist circumference (68 ± 11 and 61 ± 12 cm, p = 0.034), blood concentration of C-reactive protein (2.3 ± 1 and 0.9 ± 0.7 mg/ml, p <0.001), diastolic blood pressure (70 ± 7 and 65 ± 6 mm Hg, р = 0.028), uric acid (0.29 ± 0.06 and 0.21 ± 0.06 mmol/L, р = 0.021), glucose (4.8 ± 0.6 and 4.6 ± 0.6 mmol/L, p = 0.011), triglycerides (0.86 ± 0.37 and 0.72 ± 0.31 mmol/L, р = 0.017), and lower mean level values of highdensity lipoprotein cholesterol (1.38 ± 0.36 and 1.58 ± 0.31 mmol/L, p = 0.011) were noted. Multivariate regression analysis showed an independent  relationship between the 25(ОН)D level, C-reactive  protein level (β = -0.55,  p <0.001),  and HOMA index (β = -0.96, p < 0.001).Conclusion. A low vitamin D level in the blood serum in children is associated with the components of the metabolic syndrome.